2020
DOI: 10.33594/000000219
|View full text |Cite
|
Sign up to set email alerts
|

Human Adipose-Derived Pericytes: Biological Characterization and Reprogramming into Induced Pluripotent Stem Cells

Abstract: This article is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…CD146 is known to be an endothelial/pericyte marker that acts as a receptor for angiopoietin-like protein 2 (ANGPTL2) and has been implicated in promoting obesity by enhancing adipogenesis and lipogenesis [ 78 , 80 ]. Pericytes play a role in the development and maintenance of blood-vessel integrity, as well as the control of immune-cell-trafficking across the vessel walls [ 81 , 82 ]. The increased expression of a pericyte marker observed in this study indicated the remodeling of the vasculature at the capillary level, which may be one of the many factors responsible for the lipedema phenotype [ 78 ].…”
Section: Mechanisms Implicated In the Pathogenesis Of Lipedemamentioning
confidence: 99%
“…CD146 is known to be an endothelial/pericyte marker that acts as a receptor for angiopoietin-like protein 2 (ANGPTL2) and has been implicated in promoting obesity by enhancing adipogenesis and lipogenesis [ 78 , 80 ]. Pericytes play a role in the development and maintenance of blood-vessel integrity, as well as the control of immune-cell-trafficking across the vessel walls [ 81 , 82 ]. The increased expression of a pericyte marker observed in this study indicated the remodeling of the vasculature at the capillary level, which may be one of the many factors responsible for the lipedema phenotype [ 78 ].…”
Section: Mechanisms Implicated In the Pathogenesis Of Lipedemamentioning
confidence: 99%
“…ASCs represent the most interesting population in the field of regenerative medicine, as they are involved in the maintenance of the tissue metabolic balance, angiogenesis, wound healing, and scar reparation [ 34 , 35 , 36 , 37 , 38 ] by also contributing, in synergy with pericytes and EPCs, to sustaining the capillaries of the vascular network [ 36 , 39 ]. Pericytes or perivascular cells retain strong differentiation and angiogenic potential, as recently discovered by Ahmed and colleagues [ 40 ], since they display similar characteristics to MSCs and are crucial for ECs’ survival, migration, and growth support [ 41 , 42 , 43 ]. No other variations in terms of cellular concentrations or cellular viability were found in this study, suggesting that processing samples with a standardized GMP-compliant protocol could better characterize the biological parameters important for further use of these cells as ATMPs, as we have previously shown in a collaborative study [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The resulting MFAT product acts as an ideal scaffold of AT, containing growth factors and ASCs activated through mechanical forces. 30,62 Importantly, MFAT maintains the microvascular architecture necessary for optimal functioning of ASC paracrine properties. 63…”
Section: Isolation Methodsmentioning
confidence: 99%